Vitro and in silico antifungal efficacy of nitrogen- doped carbon nanohorn ( NCNH) against rhizoctonia solani - Dharni, Seema; Sanchita; Unni, SreeKuttan M.; Kurungot, Sreekumar; Samad, Abdul; Sharma, Ashok; Patra, Dharani Dhar (Journal of Biomolecular Structure & Dynamics, 2016)
We have investigated in vitro antifungal efficiency of nitrogen-doped carbon nanohorn (NCNH) against Rhizoctonia solani (R. solani) plant pathogenic fungi. NCNH with size of 50-60nm and concentrations of 10, 50, 100, and 150gmL(-1) were used. The results showed that growth of fungi in the presence of NCNH was significantly (p>.05) inhibited at 150gmL(-1) (85.13 +/-.97) after 72h. The results were validated through computational approaches. Molecular docking analysis of NCNH with endochitinase protein of R. solani was performed to validate the potential of antifungal activity of NCNH. Docking results showed different conformations of interaction of NCNH with endochitinase enzyme. The conformation with least binding energy -13.54kcal/mol was considered further. It is likely that NCNH interacts with the pathogens by mechanically wrapping, which may be one of the major toxicity actions of NCNH against R. solani. The analysis showed that NCNH might interwinds to endochitinase of R. solani leading to the deactivation of the enzyme. To best of our knowledge, this is the first report of antifungal efficacy of NCNH against R. solani and provides useful information about the application of NCNH in resisting crop disease.
Keywords: docking; endochitinase; nitrogen-doped carbon nanohorn; Rhizoctonia solani